2004
DOI: 10.1080/15459620490471616
|View full text |Cite
|
Sign up to set email alerts
|

Personal Exposures to Inorganic and Organic Dust in Manual Harvest of California Citrus and Table Grapes

Abstract: The aim of this study was to determine characteristics of personal exposure to inorganic and organic dust during manual harvest operations of California citrus and table grapes. Personal exposures to inhalable dust and respirable dust were measured five times over a 4-month period of harvesting season. We analyzed components of the dust samples for mineralogy, respirable quartz, endotoxin, and total and culturable microorganisms. Workers manually harvesting were exposed to a complex mixture of inorganic and or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 15 publications
0
13
1
Order By: Relevance
“…During citrus harvesting in Tulare County (see Fig. 1), Lee et al (2004) reported average endotoxin and total bacteria and fungi levels of 293.2 endotoxin units (EU)/m 3 and 1.9 × 10 8 organisms/m 3 , respectively, based on the total suspended particles (TSP) dislodged from polycarbonatemembrane filters. They also measured 13,787 and 13,274 colony forming units (CFU)/m 3 for culturable bacteria and fungi, respectively, using Andersen two-stage bioaerosol samplers.…”
Section: Introductionmentioning
confidence: 99%
“…During citrus harvesting in Tulare County (see Fig. 1), Lee et al (2004) reported average endotoxin and total bacteria and fungi levels of 293.2 endotoxin units (EU)/m 3 and 1.9 × 10 8 organisms/m 3 , respectively, based on the total suspended particles (TSP) dislodged from polycarbonatemembrane filters. They also measured 13,787 and 13,274 colony forming units (CFU)/m 3 for culturable bacteria and fungi, respectively, using Andersen two-stage bioaerosol samplers.…”
Section: Introductionmentioning
confidence: 99%
“…5) In previous studies of dust exposure in vineyards, exposure levels were measured during only a few operations, typically during harvest, and were extrapolated as representative exposures. 5,6) Grape workers demonstrated a reduced vital capacity consistent with restrictive pulmonary function from mixed-dust exposure in this population.…”
Section: )mentioning
confidence: 73%
“…[5][6][7] However, these estimations were based on only a few measurements or indirect evidence of health effects. Agricultural workers perform many operations and the exposure among operations can vary significantly.…”
Section: )mentioning
confidence: 99%
“…The researchers found that the workers were exposed to a complex mixture of organic and inorganic particles during manual harvest of citrus and table grapes (Lee et al, 2004). Geometric means for inhalable dust and respirable dust were 39.7 mg m -3 and 1.14 mg m -3 , respectively during citrus harvest, which were significantly higher compared to the levels that were determined for table grape operations and exceeded the TLVs for inhalable dust and respirable quartz.…”
Section: Orchards and Vegetable Growingmentioning
confidence: 88%
“…During mechanical harvest of almonds, dust levels in the dust plume were 26513 mg m -3 and 154 mg m -3 , respectively for inhalable dust and respirable dust (Lee et al, 2004). Mechanical harvesting of tree crops caused average personal exposure of 52.7 mg m -3 of inhalable dust and 4.5 mg m -3 of respirable dust.…”
Section: Orchards and Vegetable Growingmentioning
confidence: 99%